2023
DOI: 10.3390/ijerph20032759
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of the GATT Procedure in Open-Angle Glaucoma—6-Month Results

Abstract: AIM. The aim of the study was to retrospectively evaluate the efficacy and safety of GATT during a 6-month observation period. MATERIAL AND METHODS. The studied group consisted of 69 open-angle glaucoma patients treated with GATT as the only procedure or in combination with cataract surgery. Patients were assessed 1 day, 10 days, 1 month, 3 months, and 6 months after the surgery via standard ophthalmic examination including VF, IOP, and BCVA. The number of medications taken daily and possible complications wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The rate of hyphema after GATT has been reported to be 51 % at POD1, 16–30 % at POW1, and 1–6% at POM1. 5 , 6 Delayed-onset reflux hyphemas have been reported in eyes with prior angle surgery in the absence of trauma. 2 , 3 , 7 Ahuja et al reported a series of 12 patients with symptomatic hyphema 2–31 months after Trabectome® (NeoMedix Corp., Tustin, CA) surgery, wherein most patients reported preceding physical exertion or sleeping on the operative side.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of hyphema after GATT has been reported to be 51 % at POD1, 16–30 % at POW1, and 1–6% at POM1. 5 , 6 Delayed-onset reflux hyphemas have been reported in eyes with prior angle surgery in the absence of trauma. 2 , 3 , 7 Ahuja et al reported a series of 12 patients with symptomatic hyphema 2–31 months after Trabectome® (NeoMedix Corp., Tustin, CA) surgery, wherein most patients reported preceding physical exertion or sleeping on the operative side.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated significant IOP reduction and reduced reliance on anti-glaucoma medications following GATT, with a favorable safety profile and minimal adverse events such as transient hyphema and IOP spikes [ 53 , 54 ]. While GATT is effective and adaptable, it carries unique complications such as an increased risk of hyphema from the extensive unroofing of Schlemm’s canal [ 55 ]. Typically, these transient events resolve spontaneously or with conservative management, and postoperative IOP spikes are generally well controlled with medication.…”
Section: Devices Procedures and Surgical Techniquesmentioning
confidence: 99%